Modulation of Growth and Antioxidative Defense Mechanism in Wheat (Triticum aestivum L.) Mediated by Plant-Beneficial Strain Pseudomonas veronii MR-15 under Drought Conditions - Maryam Rehman; Muhammad Shahid; Saqib Mahmood; Qasim Ali; Muhammad Azeem (Applied Sciences, 2023)
Drought stress severely influences plants in various ways and is considered an alarming threat to sustainable crop production worldwide. However, plant-growth-promoting rhizobacteria (PGPRs) have the natural ability to tolerate drought and enable plants to induce stress resistance by altering critical metabolic pathways. In this study, we isolated and characterized a drought-tolerant rhizobacterium from the ground nut (Arachis hypogaea). Sequencing of the 16S rRNA gene traced its lineage to Pseudomonas veronii, named MR-15. The strain exhibited natural capabilities to solubilize phosphate, produce indole acetic acid, and grow a drought medium containing PEG (polyethylene glycol). The seeds of two wheat varieties (Triticum aestivum) inoculated with MR-15 were grown under drought and fully hydrated conditions and showed a significant increase in plant biomass, enhanced cellular antioxidant enzyme activity, and reduced reactive oxygen species. The MR-15 strain also significantly increased pigmentation and protein contents compared to plants raised from seeds grown without inoculation. These beneficial effects were consistent under drought stress conditions, indicating that MR-15 effectively alleviated wheat plants from drought-induced cellular oxidative damage. The findings suggest that MR-15 has the potential to serve as a biofertilizer, and further experiments should be conducted to explore its role in promoting plant growth and yield under drought conditions, particularly in semi-arid and arid zones. This is the first study reporting Pseudomonas veronii as a potential PGPR strain.